PENULIS SUNDA SEBAGAI PELESTARI BUDAYA - Susanti, Santi; Mulyana, Deddy; Damayani, Ninis Agustini (Universitas Padjadjaran, 2013)
This research aims to find out motives to become Sundanese Writers, self meaning construction of Sundanese Writers as culture preservators and message presenting process of Sundanese Writers as culture preservators. This research used qualitative method with a phenomenological approach. Data was gainedÂ throughÂ a series of indepth interviews with eight informants as Sundanese Writers in Bandung City, and also from nonparticipant observation and literature study. The informants of this research are classified into two types, these are Sundanese Culture Inheritors and Sundanese Culture Developers. The results of this study indicated that the main motive to become a Sundanese Writers is idealism, which consists of aspects of driving and the aspects of expectation. The self meaning of Sundanese Writers as culture preservators was constructed into two types, these are Sundanese Culture Inheritors and Sundanese Culture Developers. Message presenting process of Sundanese Writers as culture preservators were done by involving steps commonly done by writers to produce a writing. Penelitian ini bertujuan menemukan motif menjadi Penulis Sunda, konstruksi makna diri Penulis Sunda sebagai pelestari budaya dan proses penyampaian pesan Penulis Sunda sebagai Pelestari Budaya. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan studi fenomenologi. Data diperoleh melalui wawancara mendalam dengan delapan Penulis Sunda yang berada di Kota Bandung, juga melalui observasi nonpartisipan dan studi pustaka. Hasil penelitian ini mengungkapkan bahwa motif utama menjadi Penulis Sunda adalah idealisme kesundaan, yang terbagi ke dalam aspek pendorong dan aspek harapan. Konstruksi makna diri Penulis Sunda sebagai pelestari budaya terbagi menjadi Pewaris Budaya Sunda dan Pengembang Budaya Sunda. Proses penyampaian pesan Penulis Sunda sebagai Pelestari Budaya dilakukan melalui tahapan yang umum dilakukan penulis untuk menghasilkan suatu tulisan.